The effects of hotel customer-based experience, motivation factors and brand image on hotel loyalty in Iran / Yeganehsadat Hosseini - Hosseini, Yeganehsadat (Institute of Graduate Studies, UiTM, 2018)
Hospitality industry is one of the most substantial factors for the tourism industry in Iran. However, this sector has been neglected for various political and social reasons, especially, during the post- Islamic revolution of 1979. Therefore, findings from this present study contributes to the improvement of both hotel management and tourism industry in Iran. The ANOVA results of the present study were obtained from 302 international and local guests in four and five star hotels in five major cities in Iran. The main objective of this study is to investigate the effects of hotel customer-based experience, motivation factors and brand image dimensions on hotel loyalty and also to propose a model for the hotel industry in Iran. The findings for regression Model 1 show that customer experience (indirect experience, direct experience and traveller's motivation) influences brand association. The first three variables made a statistically significant contribution (< 0.001) are service performance (β=.43), advertising efforts (β=.32) and traveller's motivation factors (β=.31). However, Word-of-mouth did not make a unique contribution of the variable. While regression Model 2 shows customer experience (indirect experience, direct experience and traveller's motivation) influences quality of experience and made a statistically significant contribution (< 0.001)…